The effect of language experience on perceptual normalization of Mandarin tones and non-speech pitch contours - Luo, Xin (Acoustical Society of America, 2014)
Context-dependent pitch perception helps listeners recognize tones produced by speakers with different fundamental frequencies (f0s). The role of language experience in tone normalization remains unclear. In this cross-language study of tone normalization, native Mandarin and English listeners were asked to recognize Mandarin Tone 1 (high-flat) and Tone 2 (mid-rising) with a preceding Mandarin sentence. To further test whether context-dependent pitch perception is speech-specific or domain-general, both language groups were asked to identify non-speech flat and rising pitch contours with a preceding non-speech flat pitch contour. Results showed that both Mandarin and English listeners made more rising responses with non-speech than with speech stimuli, due to differences in spectral complexity and listening task between the two stimulus types. English listeners made more rising responses than Mandarin listeners with both speech and non-speech stimuli. Contrastive context effects (more rising responses in the high-f0 context than in the low-f0 context) were found with both speech and non-speech stimuli for Mandarin listeners, but not for English listeners. English listeners' lack of tone experience may have caused more rising responses and limited use of context f0 cues. These results suggest that context-dependent pitch perception in tone normalization is domain-general, but influenced by long-term language experience.